2001
DOI: 10.1144/gsl.sp.2001.186.01.10
|View full text |Cite
|
Sign up to set email alerts
|

Geometric controls on the evolution of normal fault systems

Abstract: The growth of normal fault arrays is examined in basins where sedimentation rates were higher than fault displacement rates and where fault growth histories are recorded by thickness and displacement variations within syn-faulting sequences. Progressive strain localization is the principal feature of the growth history of normal faults for study areas from the Inner Moray Firth, a sub-basin of the North Sea, and from the Timor Sea, offshore Australia. The kinematics of faulting are similar in both study areas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…For the Jurassic reservoir-bounding fault planes with dips of 60 to 65°(consistent throughout the modeled area), the amount of extensional deformation (heave) can be estimated as proportional to the accumulated throw. As expected from results from Zhang et al (2009) and previous empirical observations and numerical models (Cowie, 1998;Walsh et al, 2001;Meyer et al, 2002;Gartrell et al, 2006), a strong correlation between initial fault length and the amount of accumulated throw during extensional reactivation exists. Larger faults (F1, F4, and F5) accommodated most of the extensional deformation, reflected as higher throws The height of the larger faults F1, F4, and F5 was initially set so that they reached the top surface (i.e., maximum possible height); this parameter most probably influences the outcome of the modeling (see below) in addition to the other major control from the fault strike lengths.…”
Section: Fault-throw Distributionsupporting
confidence: 80%
“…For the Jurassic reservoir-bounding fault planes with dips of 60 to 65°(consistent throughout the modeled area), the amount of extensional deformation (heave) can be estimated as proportional to the accumulated throw. As expected from results from Zhang et al (2009) and previous empirical observations and numerical models (Cowie, 1998;Walsh et al, 2001;Meyer et al, 2002;Gartrell et al, 2006), a strong correlation between initial fault length and the amount of accumulated throw during extensional reactivation exists. Larger faults (F1, F4, and F5) accommodated most of the extensional deformation, reflected as higher throws The height of the larger faults F1, F4, and F5 was initially set so that they reached the top surface (i.e., maximum possible height); this parameter most probably influences the outcome of the modeling (see below) in addition to the other major control from the fault strike lengths.…”
Section: Fault-throw Distributionsupporting
confidence: 80%
“…Our improving understanding of the scaling relationships between fault attributes such as length, width, magnitude of displacement and interconnectivity suggests that these factors will additionally influence the processes of fault growth and reactivation (e.g. Cowie & Scholz 1992;Somette et al 1993;Walsh et al 2001).…”
Section: Regime Jmentioning
confidence: 99%
“…Studies of these evolving and mature rifts have recognized progressive strain localization as an important process in rift evolution on a variety of temporal and spatial scales. It is commonly thought that rifts develop an initially broad zone of complex deformation that becomes localized onto a smaller number of discrete and increasingly large faults [ Walsh et al ., ; Cowie et al ., ], while sedimentation becomes focused into fewer, larger depocenters [ Gawthorpe and Leeder , ; Gawthorpe et al ., ; Cowie et al ., ]. Furthermore, it has been shown that active faulting and strain migrate toward the rift axis with increasing extension, resulting in rift narrowing [ Gawthorpe et al ., ; Cowie et al ., ].…”
Section: Introductionmentioning
confidence: 99%